Application of the Global Burden of Animal Diseases methods at country level: experiences of the Ethiopia case study - Jemberu, Wudu T.; Chaters, G.; Asfaw, W.; Asteraye, Girma B.; Amenu, Kebede; Huntington, B.; Rushton, J.; Knight-Jones, Theodore J.D. (World Organisation for Animal Health, 2024)
Animals play a central role in human livelihoods and welfare. Animal diseases have a great impact on the benefits humans derive from animals and can also pose a risk to human health. Better control of animal diseases generates wider societal benefits, including reducing the climate and ecological impacts of livestock and improving animal welfare. To better understand the scale of investment justified for the control and prevention of animal disease, the wide-ranging impacts of disease on animal production and health must be measured. The Global Burden of Animal Diseases (GBADs) programme is quantifying animal disease burden from the local to global levels. The GBADs programme includes country case studies for national- and local-level analysis. Ethiopia is the first case study country in which GBADs methods have been applied. GBADs’ Ethiopia case study consists of three activity areas: i) stakeholder engagement; ii) livestock disease burden estimation, including data collection, analytics, evidence generation and communication; and iii) capacity building in animal health economics. At the start of the case study, various stakeholder communication platforms were used to familiarise stakeholders with GBADs and engage their support in various ways, including data access, and, through this engagement, to ensure the programme tools and outputs were relevant and useful to their needs. Existing data were retrieved from multiple sources and used to estimate disease burden. This process involved multiple steps, including estimation of biomass and economic value, the Animal Health Loss Envelope (farm-level disease burden), wider economic impacts and attribution of the disease burden to different levels of causes. This was carried out for major livestock species (cattle, sheep, goats and poultry) in Ethiopia. Capacity building on animal health economics was carried out for GBADs end users to increase competence in utilising animal health economic evidence, including GBADs outputs. This article documents experiences of the implementation of these activities in the GBADs Ethiopia case study.